1937
DOI: 10.1021/j150379a012
|View full text |Cite
|
Sign up to set email alerts
|

On the Photographic Infra-red Spectrum of Methylacetylene (Allylene) and the C–C Single Bond Distance.

Abstract: In a series of investigations of the absorption spectra of simple polyatomic molecules in the photographic infra-red we have included methylacetylene (CH3C0H) for investigation because it seems interesting from two points of view: (1) As it was to bo expected that the molecule represents a symmetrical top its investigation could serve as a check on the theory of the rotational structure of symmetrical tops in general which, so far, in the photographic infra-red, had been rather unsatisfactory. (2) As all the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

1941
1941
2001
2001

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(9 citation statements)
references
References 7 publications
2
7
0
Order By: Relevance
“…For DMA& the values of these constants are nearly identical to those obtained by fitting the data of Table 2 to Eqn. (1). The B and Dj values are therefore nearly coincident with the values plotted in Fig.…”
Section: Rotational Analysissupporting
confidence: 81%
“…For DMA& the values of these constants are nearly identical to those obtained by fitting the data of Table 2 to Eqn. (1). The B and Dj values are therefore nearly coincident with the values plotted in Fig.…”
Section: Rotational Analysissupporting
confidence: 81%
“…No important change appears permissible in the lengths of the C-C and C =C bonds, which have been determined with satisfactory accord from electron-diffraction measurements for methylacetylene and dimethylacetylene [8], and from spectroscopic measurements for methylacetylene [6,7]. The assignment of frequencies made by Crawford [9] appears to be satisfactory, as he has shown that the same potential constants reproduce the spectra of acetylene, methylacetylene, and dimethylacetylene.…”
Section: Methods and Data Used In The Calculationsmentioning
confidence: 93%
“…The value selected for the larger moment of inertia of methylacetylene was 98.276 X 10-40 g cm 2 , derived from the mean of the values of Bo reported by Herzberg, et al [6], 0.28458 cm-l , and by Badger and Bauer [7], 0.28496 cm-l . This value of the moment of inertia and the values of 1.060, 1.11 , and 1.207 angstrom units for the lengths of the acetylenic C-H, the methyl C-H, and the acetylenic C=C, bonds, respectively, yield 1.462 angstrom units for the length of the C-C single bond in methylacetylene.…”
Section: Methods and Data Used In The Calculationsmentioning
confidence: 99%
“…The so-called shrinkage effect15) should disappear in regard to the ra distances, which are obtained from rg by subtracting the perpendicular and centrifugal contributions:16) (1) Since the ra structure represents the thermal-average positions of constituent atoms,4) it corresponds to the equilibrium symmetry of the molecule. In other words, provided the molecular symmetry is known from spectroscopy, the number of distance parameters (ra) can be decreased by assuming the symmetry as a constraint.…”
Section: Discussionmentioning
confidence: 99%